2018
DOI: 10.1016/j.jtcvs.2017.09.147
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome following concomitant mitral valve surgery and Cox maze procedure for atrial fibrillation

Abstract: This study suggests that the addition of CM to mitral valve procedures, even with a high degree of complexity, did not increase operative risk. In long-term follow-up, the CM procedure demonstrated acceptable rhythm success, reduced AF burden, and remarkably low stroke rate. Individual surgeon experience and training may notably influence long-term surgical ablation for AF success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 28 publications
1
52
0
1
Order By: Relevance
“…The answer is yes. Ad and colleagues 1 report very low morbidity and mortality among the 473 patients in this series who underwent combined ablation and mitral valve surgery. 2.…”
Section: Is Ablation Safe?mentioning
confidence: 67%
“…The answer is yes. Ad and colleagues 1 report very low morbidity and mortality among the 473 patients in this series who underwent combined ablation and mitral valve surgery. 2.…”
Section: Is Ablation Safe?mentioning
confidence: 67%
“…Caswell et al [3] demonstrated that postoperative AF was a risk factor of cardioembolic stroke after valve replacement, and restoration of sinus rhythm is considered to be bene cial for improving long-term outcomes [4]. Surgery for AF has been shown to be feasible and effective, and does not increase perioperative morbidity and mortality when combined with other cardiac procedures [5] [6] [7]. While effective, the Coxmaze III procedure has limitations for the treatment of AF, as it is both invasive and time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Caswell et al [ 3 ] demonstrated that postoperative AF was a risk factor of cardioembolic stroke after valve replacement, and restoration of sinus rhythm is considered to be beneficial for improving long-term outcomes [ 4 ]. Surgery for AF has been shown to be feasible and effective, and does not increase perioperative morbidity and mortality when combined with other cardiac procedures [ 5 – 7 ]. While effective, the Cox-maze III procedure has limitations for the treatment of AF, as it is both invasive and time consuming.…”
Section: Introductionmentioning
confidence: 99%